2022
DOI: 10.1111/iju.14981
|View full text |Cite
|
Sign up to set email alerts
|

Delta neutrophil index as a prognostic factor for mortality in patients with Fournier's gangrene

Abstract: Objectives The delta neutrophil index represents the fraction of circulating immature granulocytes and is a marker of infection and sepsis. Our study aimed to evaluate the usefulness of the delta neutrophil index in predicting mortality in patients with Fournier's gangrene. Methods We enrolled patients with Fournier's gangrene who were admitted to the Wonju Severance Christian Hospital (Wonju, Korea) between September 2010 and December 2021. We retrospectively analyzed the patients' characteristics, factors re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Most of the studies examined the usefulness of the DNI to predict various outcomes in patients with inflammation-related diseases such as cholecystitis, pancreatitis, abscess, and Fournier’s Gangrene, demonstrating similar results. [ 136 137 138 139 140 ] Nevertheless, given that these studies typically have a single-center focus and involve a limited number of patients, it is important to replicate these findings in diverse settings to obtain a definitive conclusion.…”
Section: Delta Neutrophil Indexmentioning
confidence: 99%
“…Most of the studies examined the usefulness of the DNI to predict various outcomes in patients with inflammation-related diseases such as cholecystitis, pancreatitis, abscess, and Fournier’s Gangrene, demonstrating similar results. [ 136 137 138 139 140 ] Nevertheless, given that these studies typically have a single-center focus and involve a limited number of patients, it is important to replicate these findings in diverse settings to obtain a definitive conclusion.…”
Section: Delta Neutrophil Indexmentioning
confidence: 99%
“…The DNI is derived by quantifying the variance between leukocyte differentials measured in the myeloperoxidase and lobularity/nuclear density channels, providing an indication of the proportion of immature granulocytes present in the bloodstream [ 21 ]. Numerous studies have demonstrated that the DNI can serve as a valuable biomarker in predicting disease severity and prognosis in patients with diverse infectious conditions or sepsis [ 3 , 22 , 23 ]. However, the DNI was not an independent predictor in this study, although it was significantly higher in nonsurvivors in the univariate analysis.…”
Section: Discussionmentioning
confidence: 99%
“…It is also known as necrotizing fasciitis of the perineum and can be life-threatening if left untreated. This condition is more common in men than in women [ 2 ], and usually occurs in people with weakened immune systems or other underlying health conditions [ 3 ]. It is often caused by bacteria such as Escherichia coli , Klebsiella , and Pseudomonas aeruginosa [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…DNI is a laboratory parameter that measures the difference between the fraction of immature granulocytes and mature granulocytes in the bloodstream (8)(9)(10). DNI is a sensitive marker of systemic inflammation and infection and has been shown to be a promising prognostic biomarker in various cancers, including EC (10)(11)(12)(13)(14). Furthermore, DNI can be used as a predictive biomarker for the development of EC in women with endometrial hyperplasia.…”
Section: Introductionmentioning
confidence: 99%